Second Sphere Effects of O2 Activation in Stearoyl-Acyl Carrier Protein Delta9 Desaturase - Ng, Yi Han (My University, 2008)
Stearoyl-acyl carrier protein Delta9 desaturase (Delta9D) from Ricinus communis converts stearic acid into monounsaturated oleic acid and functions to maintain the lipid composition of the cell membrane. While the desaturase active site glutamate and histidine residues are crucial to catalysis, there are a number of conserved "second sphere" residues. One such residue is Threonine 199 found ~5Angstroms from the diiron center and it has been hypothesized to stabilize the peroxo intermediate formed during catalysis. In this work, the role of this residue has been probed through studies of a series of mutants. These mutations show a lower kcat and an increase in the rate of decay of the peroxo intermediate, providing evidence of stabilization of the intermediate.
18 p.
Keywords: Biochemistry; Microbiology